BIOTECHNOLOGICAL IMPROVEMENT OF CASSAVA YIELD AND PROCESSING FOR FOOD SUSTAINABILITY IN NIGERIA - Udebuani, Angela Chika; Ukachukwu, Chidinma Ogochukwu (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Cassava (Manihot esculenta) was introduced into Nigeria by Portuguese merchants in 1501. Since then, it has become a major source of food and raw materials leading to an increase in demand. In Nigeria, two-thirds of the States, mainly in the southern region, produce cassava. Malnutrition among the rural populace, especially children and women has led scientists to device means of increasing the nutritional content and varieties of cassava for food sustainability in Nigeria. Many genetically modified cassava species are produced and marketed in Nigeria. Today we have varieties with vitamin A, reduced carbohydrate content, disease resistance to mention but a few.